Matter and technique. A conversation with Miguel Ángel Alonso del Val - Labarta Aizpún, Carlos (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2015)
The generation of architects that replaced our modern masters reached professional and academic maturity some time ago. In the 1970s they were learning under the very close shadow of Carvajal, Oíza and Sota. And with their unbreakable faith in architecture, they have managed  to pass the baton to new generations. For some time they have been professors, and now even have disciples teaching in various Spanish schools. Among their number is Miguel Ángel Alonso del Val, the Professor of Design at the School of Architecture of the University of Navarre, who has followed his path with assured silence and without the haste that occasionally troubles the most insecure. Also a disciple of Frampton at Columbia University, he never separated his discourse from the tectonic values of construction and he began to weave his career with research on architectural design. Few architects of his generation have managed such a solid balance between research, teaching and professional practice. That is why this conversation, on the materiality of both his own and others’ projects, represents an opportunity to continue delving into their values and implications. The conversation took place in the office of the head of the School of Architecture of the University of Navarre, the new post—yet another—he has just accepted, and it gives us a chance to reflect on issues as crucial for architecture as matter and technique.